The Hydrothermal Autoclave Synthesis of the Nanopowders of the Refractory ZrO2 and HfO2 Oxides - N.F. Karpovich; M.A. Pugachevsky; V.I. Panfilov; A.P. Kuzmenko; M.B. Dobromyslov (Журнал нано- та електронної фізики)
The nanopowders of the transition metal ZrO2 and HfO2 oxides were obtained by the hydrothermal autoclave synthesis. The nanoparticles possess a rounded shape and a size range of 40 to 80 nm (ZrO2), of 10 to 40 nm (HfO2). X-ray diffraction analysis and electron microscopy show that the structure of the nanoparticles is monoclinic.